Path Dependency of Plastic Deformation in Crystals: Work Hardening, Crystallographic Rotation and Dislocation Structure Evolution - Zhen-Wei Zhang; Zheng Li; Ying Liu; Jing-Tao Wang (Crystals, 2022)
This paper reviewed the research progress of studies on the crystal rotation of single crystals that were deformed by tension and shear and the influences of crystal rotation and dislocation evolution on strain hardening behavior in crystals that were deformed with different initial orientations. The crystal rotation is entirely different depending on whether the single crystal was deformed by tension or shear. A three-stage work hardening behavior, which is not one of the intrinsic properties of materials, is generated when FCC metallic single crystals are deformed by tension along unstable oriFigurFigurentations, but single crystals do not exhibit this three-stage hardening behavior when they are deformed by simple shear at room temperature. Under tension, crystal rotation causes the transition from work hardening stage I to stage II, while the transition from work hardening stage II to III is caused by dislocation evolution. The evolution of the dislocation structure is related to deformation loading and can be classified into three types when a crystal is deformed by tension. Different from tension, shear stress can directly act on one of the 12 slip systems when a crystal is deformed by simple shear. When FCC single crystals are deformed by shear along the (1<semantics><mover accent="true">1¯</mover></semantics>1)[110], (111)[11<semantics><mover accent="true">2¯</mover>]</semantics> and (001)[110] orientations, the single slip system, co-planar slip systems and co-directional slip systems are activated, respectively, and the crystals hardly rotate under the shear conditions. The slip direction of [110] forces the crystal to rotate toward the shear direction under simple shear. The dislocation tangles tend to form the dislocation cells and wall structures when multiple slip systems are activated under simple shear.